Pelatihan Efisiensi Penggunaan Canva sebagai Media Pembelajaran Digital untuk Meningkatkan Literasi Guru di Kabupaten Maros - Zaki, Ahmad; Sutamrin; Nasir, Norma; Rahayu, Ayu; Eka Kartika, Andi (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The advancement of digital technology requires teachers to possess strong digital literacy skills to create learning experiences that are creative, efficient, and aligned with the needs of 21st-century students. However, many teachers in regional areas still face challenges in utilizing technology due to limited infrastructure and a lack of technical knowledge. This program was conducted to help teachers improve their skills in developing engaging and time-efficient digital learning media through training on the efficient use of Canva, aiming to strengthen teachers’ digital literacy and support the transformation of classroom learning. The training was implemented in four stages: needs analysis, face-to-face training, post-training mentoring, and evaluation. The needs analysis was carried out through an online survey to assess teachers’ initial digital skills. The face-to-face training was conducted for one full day at the SMPN 1 Maros auditorium and involved 15 teachers (11 mathematics teachers and 4 from other subjects). Using a hands-on approach, the training focused on introducing Canva’s features, strategies for utilizing templates, visual design principles, and integrating the media into online learning platforms. Post-training mentoring was conducted over two weeks via an online group and consultation sessions with facilitators. The results showed that all participants successfully created at least one digital learning product that was more visually appealing and efficient, and these products received positive responses from students. This program demonstrates that short, hands-on training combined with online mentoring is effective in enhancing teachers’ digital literacy and fostering their active participation in developing creative digital learning materials.